(untitled) (Journal of Global Humanities and Social Sciences, 2025)
The footsteps of information technology are constantly moving forward, and for various industries, the popularity of information technology brings both opportunities and challenges. In the environment of the information age, how libraries can sustain their development and progress is the primary issue for managers to consider now. As people have more and more free time, they come to the library to read more and more frequently, and as we use the library more and more, there are newer and higher demands for library management and services. This requires libraries to keep pace with the times, change the backward management and services, innovate the concept of management and services, the way and the details of them to meet the growing needs of people and provide better services for people to have a better reading experience.